Harbin and Parisian “Notes”: the Originality of Sound - Proskurina, Elena (Literatūra, 2021)
The article is an attempt at a comparative analysis of two emigrant “notes”. Both of them have already been studied separately in detail by literary scholars. However, a comparison of these two phenomena has not yet received sufficient coverage in science. This work presents the socio-historical context of each of the “notes”. It shows the influence of this context on the creative consciousness of authors, poetics, literary correlates. While one of the characteristic features of the “Parisian note” is the scarcity of literary authorities, the poetry of the “Harbin note”, on the contrary, is distinguished by its receptive breadth. The relationship of Russian Parisians with European culture is a failed dialogue. In addition to the focus on lyrical documentary, initiated by the theorist of the “note” G. Adamovich, this became one of the reasons for the asceticism of his poetics. “Harbin note” was created in a different socio-cultural atmosphere. Unlike Paris, China has become a second home for the Russian Harbinians. This explains vital poetic colors in the poetry of the “Harbin note”. Paris is most often painted by the representatives of the “Parisian note” in the colors of death. The poetry of China occupies a special place among the poetic attractions of the “Harbin note”. This was reflected in the linguistic wealth of the Harbin poets. Thus, in contrast to the “Parisian note”, the “Harbin note” demonstrates the literary transfer that took place with the country of residence.
Keywords: literature of the first emigration; “Parisian note”; “Harbin note”; cultural dialogue; literary transfer; emigrant myth